Personalizing Emoji Meaning and Use in Digital Communication - Buczek-Zawiła, Anita (Papers in Linguistics, 2024)
Communication via digital media is characterized by growing use of graphic elements employed to convey emotions and concepts in a succinct form, especially in interpersonal interactions. Emoji are naturally ambiguous in meaning, which undergoes various modifications. One way of incorporating emoji into interpersonal communication is repurposing their meaning and use, so that a shared personal meaning develops between individual users or within small groups. The article explores novel and unique applications of certain emoji in an independent (conceptual) replication study of Wiseman and Gould’s work (2018). The present study analyzes the data obtained via a web-based survey in a group of 132 respondents aged 17 to 55+ to subsequently get to know their motivations behind the repurposed use of emoji. It is demonstrated how this adaptation of graphic icons helps people express their likes and preferences, romantic feelings, amusement, and, as a result, can aid users in building closer relationships in micro-communities. In essence, the article is intended to contribute to a better understanding of emoji use in multimodal interpersonal communication.